The Open-Multinet Upper Ontology Towards the Semantic-based Management of Federated Infrastructures - Willner, Alexander; Papagianni, Chrysa; Giatili, Mary; Grosso, Paola; Morsey, Mohamed; Al-Hazmi, Yahya; Baldin, Ilya (EAI Endorsed Transactions on Scalable Information Systems, 2015)
The Internet remains an unfinished work. There are several approaches to enhancing it that have been experimentally validated within federated testbed environments. To best gain scientific knowledge from these studies, reproducibility and automation are needed in all areas of the experiment life cycle. Within the GENI and FIRE context, several architectures and protocols have been developed for this purpose. However, a major open research issue remains, namely the description and discovery of the heterogeneous resources involved. To remedy this, we propose a semantic information model that can be used to allow declarative interoperability, build dependency graphs, validate requests, infer knowledge and conduct complex queries. The requirements for such an information model have been extracted from current international Future Internet research projects and the practicality of the model is being evaluated through initial implementations. The main outcome of this work is the definition of the Open-Multinet Upper Ontology and related sub-ontologies, which can be used to describe and manage federated infrastructures and their resources.
Keywords: ontology; testbed; federation; semantic; management